Legal limits of the autonomy of higher education institutions while developing educational programs - Varych, O.; Savokhina, M. (Problems of Engineer-Pedagogical Education, 2019)
The article deals with the issues of the legal regulation of the activities of higher education institutions in the development, implementation, monitoring, updating and revision of educational programs. The paper mentions the features of the implementation of the powers of higher education institutions within the context of such legal constructions as "the limits of legal regulation" and "restriction of rights". The elements of each direction of the autonomy of institutions of higher education in the formation of educational programs are analyzed in detail. The mechanism of implementation of the provisions of general and special laws in the field of higher education in the local legal acts is considered, namely the main directions which should form the internal regulatory framework; the necessity of higher education teachers’ and students’ participation in the given process is substantiated. The process of creating specializations, the procedure for their approval by the Academic Council of higher education institutions, the specifics of the creation of specialization groups, the structure and distribution of responsibilities in such groups in the creation of specializations, their participation in constructing and implementing educational programs are analyzed. Clear boundaries, forms and directions of formalization of the real legal relations that arise at the present stage of development of higher education in the field of formation of educational programs through the prism of the implementation of the principle of autonomy by higher education institutions are established. The provisions of general and special laws in which the legal limits of the autonomy of institutions higher education are established while developing (designing) educational programs are systematized, a comparative analysis of the influence of normative legal acts, having a higher legal force, on the formation of the local legal framework and the role of the legal service in systematization, review and updating of the internal regulations and rules of the higher education institution is conducted. In the context of monitoring, reviewing and updating educational programs, the vectors for improving the educational process are singled out while interacting with students, employers, teachers and other stakeholders who are interested in creating an effective and science-driven educational program which is as close as possible to the industry requirements.